IMPLEMENTASI KEBIJAKAN DANA DESA DALAM PELAKSANAAN DESA TANGGUH BENCANA DI DESA AIR LANANG KECAMATAN CURUP SELATAN REJANG LEBONG - Nurhidaya, Reza Okta; Rosidin, Rosidin (Yayasan Insani Mandiri Santani, 2024)
This study aims to: 1) implement village fund policies in the Disaster Tanguh Village in Air Lanang Village, South Curup District; and 2) identify obstacles to implementing village fund policies in Disaster Tanguh Village. The location of this study was Air Lanang Village in the South Curup District. This study employs qualitative descriptive research as its methodology. In this study, there are two types of data sources: primary data and secondary data. A purposive sampling technique, which is a sampling technique based on certain criteria that met the requirements of the research, was used by researchers to select research informants. Observation, interviews, and documentation were the methods used in this study to gather data. By comparing observations with data from interviews, observations, and documentation, triangulation was used in this study to test the validity of the research data. Data extraction, data presentation, and drawing conclusions are the data analysis methods used. The implementation of village fund policies in the Disaster Response Village in Air Lanang Village, Curup Selatan District, as well as communication between the chairman. Disaster Resilient Villages create good communication with the community to avoid misunderstandings. In terms of bureaucracy, it is necessary to build a separate character because it should not cause losses to the community and reduce their income. The norms that are instilled are about social norms of harmony so that the community can live in peace and peace. Key Words: Implementation, the Village Fund Policy, and Disaster Resilient Villages